2009
DOI: 10.1093/annhyg/mep061
|View full text |Cite
|
Sign up to set email alerts
|

Particle Emission and Exposure during Nanoparticle Synthesis in Research Laboratories

Abstract: Real-time size, mass and number particle concentrations, and emission rates in university laboratories producing nanoparticles by scalable flame spray pyrolysis are quantified. Measurements were conducted in four laboratories using various technological set-ups and during production of particles of a range of compositions with differing physical-chemical properties, from NaCl salt, BiPO 4 , CaSO 4 , Bi 2 O 3 , insoluble TiO 2 , SiO 2 , and WO 3 to composites such as Cu/ZnO, Cu/SiO 2 , Cu/ZrO 2 , Ta 2 O 5 /SiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Investigations on particle emissions from pilot scale flame – reactors, comparable to the one used in this study, revealed peak number concentrations in the range of 10 4 to 10 5 pt/ccm during regular particle production, what was about an order of magnitude above background concentrations [9,11]. These data represent routine working conditions.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Investigations on particle emissions from pilot scale flame – reactors, comparable to the one used in this study, revealed peak number concentrations in the range of 10 4 to 10 5 pt/ccm during regular particle production, what was about an order of magnitude above background concentrations [9,11]. These data represent routine working conditions.…”
Section: Discussionsupporting
confidence: 52%
“…in [8]). With special focus on gas – phase processes, exposure levels have been assessed during production of metal and composite particles by flame spray synthesis in an university laboratory [9], during the coating of glass compounds with CeO 2 particles derived from a flame spray process [10] and in a pilot scale particle production site [11]. As more general approach, Methner et al evaluated aerosol emissions caused by handling or synthesis of a set of different nanomaterials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Hence, potential nanospecific effects are typically not taken into account in LCA studies so far. Regarding nanosilver emissions to water, environmental concentrations depend on the applied concentration during the polymer matrix fixation and on use and disposal of the nanosilver polyester T-shirts.…”
Section: Discussionmentioning
confidence: 99%
“…56 Exposure to nanoparticles via inhalation could occur during FSP production 50 but most likely not during the particle-textile incorporation process, which takes place in a closed system. 57 Exposure during PlaSpu is unlikely as nanoparticles are produced and incorporated in a vacuum.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation leads to the formation of large agglomerates -sometimes beyond the nanosize range -which exhibit similar biological behaviour to nanoparticles upon deposition in the respiratory tract [4]. There is a large body of literature available investigating ENP release and exposure during the production of a broad range of material types, including carbon nanotubes (CNTs) and fullerenes [8][9][10][11], metals and their oxides [12,13,8,14,15,9] and nanocomposites [16].…”
Section: Activities Contributing To the Release Of Engineeredmentioning
confidence: 99%